Засоби професійного саморозвитку в системі економічної підготовки у процесі вивчення іноземних мов - Mushynska, Natalia (Dr. Viktor Koval, 2018)
Introduction.The research significance is conditioned by the fact that the problem of students’ professional self-development acquires great priority in the modern economic education. Today we aquire specialists who are capable on lifelong education, ready to expand their professional experience and possess abilities for critical thinking and problem-solving skills in a business environment. Future economist should be competitive in the conditions of innovations and rapid market changes. Aim and tasks. In the given article the system of creative tasks is presented to organize professional training of future professional and researcher, his professional creative self-development, self-actualization, self-breeding, self-realization. Research results. Summarizing the results of structural-analytical research of the contest of modern educationally-qualifying documentation, the basic requirements are distinguished and systematized to the modern bachelors of economy, who must have large cultural education, mature scientific worldview, personal integrity. They should constantly improve their professional level taking into account economic prosperity demands of Ukraine. Future economist should estimate market situation, determine the prospects of his further functioning at the market, to expose problems in financial-economic activity and develop the projects of its innovative improvement, to be structural in professionally-personality communication in different formats. Conclusion. The system of creative tasks was developed for the professional disciplines from the curricula, which realizes professional self-development of future economists by means of the tasks that enable actualization of acquired professional skills, create conditions for cognitive motivation, critical thinking, which activate motivation for professional self-development, self-perfection, self-realization. Creative tasks actualize professional self-development of future economists, enable to enrich students’ knowledge resources, their experience and intellectual-cognitive motivation for individual and professional self-development, self-perfection, self-realization.